IMF Committee on Balance of Payments Statistics : Annual Report 2004. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2005)
The IMF Committee on Balance of Payments Statistics was established in 1992 to oversee the implementation of the recommendations contained in the reports of two IMF working parties that investigated the principal sources of discrepancy in global balance of payments statistics published by the IMF; to advise the IMF on methodological and compilation issues in the context of balance of payments and international investment position statistics; and to foster greater coordination of data collection among countries. This report summarizes recent trends in global balance of payments statistics, provides an overview of statistical discrepancies in the global balance of payments statistics published by the IMF's Statistics Department, reviews the Committee's work program during 2004 (including to update the Balance of Payments Manual), and previews issues the Committee will address in the future.